RECHERCHE-ACTION ET INTELLIGENCE TERRITORIALE EN AMÉRIQUE LATINE - Mihai Pascaru (European Scientific Journal, ESJ, 2015)
The paper is an attempt at identifying significant relationships between research-action and territorial intelligence. Conceptual and methodological aspects are being considered, including their implications in intervention and action in practice. The cultural space of reference is that of Latin America where research-action has strong roots, but territorial intelligence has only recently emerged as project and territorial actoruniversity researcher partnership-based development theory and practice.